Possible Explosive Dispersal Outflow in IRAS 16076-5134 Revealed with ALMA - Guzmán Ccolque, Estrella (2022)
We present 0.9 mm continuum and CO(3-2) line emission observations retrieved from the Atacama Large Millimeter/submillimeter Array archive toward the high-mass star formation region IRAS 16076-5134. We identify 14 dense cores with masses between 0.3 and 22 M ☉. We find an ensemble of filament-like CO(3-2) ejections from −62 to +83 km s−1 that appear to arise radially from a common central position, close to the dense core MM8. The ensemble of filaments has a quasi-isotropic distribution in the plane of the sky. The radial velocities of several filaments follow a linear velocity gradient, increasing from a common origin. Considering the whole ensemble of filaments, we estimate the total mass to be 138 and 216 M ☉, from its CO emission, for 70 K and 140 K, respectively. Also, assuming a constant velocity expansion for the filaments (of 83 km s−1), we estimate the dynamical age of the outflowing material (3500 yr), its momentum (∼104 M ☉ km s−1), and its kinetic energy (∼1048-49 erg). The morphology and kinematics presented by the filaments suggest the presence of a dispersal outflow with explosive characteristics in IRAS 16076-5134. In addition, we make a raw estimate of the lower limit of the frequency rate of the explosive dispersal outflows in the galaxy (one every 110 yr), considering a constant star formation rate and efficiency, with respect to the galactocentric radius of the galaxy. This may imply a comparable rate between dispersal outflows and supernovae (approximately one every 50 yr), which may be important for the energy budget of the and the link between dispersal outflows and high-mass star formation.